Models for library management, decision-making and planning - Hayes, Robert Mayo, 1926- (Library and information science (New York, N.Y.) ;, 2001)
This book provides library managers with quantitative, qualitative, and descriptive models for decision-making, management, and planning. It consists of three major components: the application of standard 'workload factors', which provide the means for estimating staffing requirements to handle identified workloads; the estimation of workloads, for both library services and technical processing, based upon data about the populations of users and about materials acquired; and the assessment of the impact of environments external to the library (in the institution it serves, in publishing, in the national information economy), especially as determinants of the workloads. Dr. Hayes was the Dean of the prestigious UCLA Graduate School of Library and Information Science. He pioneered the merging of information science with librarianship, and he influenced the curriculum of library schools throughout the world.The book is packaged with a CD-ROM, which contains the latest version of Dr. Hayes' Library Planning Model (LPM)a theoretical and practical model for library management, including mathematics, accounting structures, and problem-solving strategies. It operates in Microsoft Excel[registered] and includes Visual Basic macros that provide a high level of menu-driven operation; it includes extensive documentation in the form of context-sensitive help screens, which provide guidance to the user at every stage of operation. The LPM can be used together with several files of sample data which allow users to compare their own results with those from other libraries. Data sets are from ARL, ACRL, academic, medical, and business libraries.